Contrasting needs of grassland dwellers: Habitat preferences of endangered beetles (Coleoptera) on the Pouzdrany steppe - Pokluda, Pavel (Jihočeská univerzita, 2010)
The Master thesis presents results of study on habitat selection of flightless steppe beetles including darkling beetle Blaps lethifera, ground-beetle Carabus hungaricus, two longicorns (Dorcadion spp.), and four oil beetle species (Meloe spp.) using pitfall traps in drygrassland fragment - the Pouzdrany steppe. This work provides description of their habitat preferences and seasonal activity pattern.
Contrasting needs of grassland dwellers: Habitat preferences of endangered beetles (Coleoptera) on the Pouzdrany steppe